Drugs that enlarge the QT interval of the electrocardiogram. - Pedro Miguel Milián Vázquez.; Masiel Cruz Rodríguez; Antonio L. Moreno Otero (Medisur)
In this article the main causes of the enlargement of the electrocardiogram QT interval are commented, making emphasis in the main cause: drugs. Some of the drugs are mentioned that produce this clinical situation, as well as the possible mechanisms that produce it. Besides, some recommendations, related with the prescription of drugs that enlarge this electrocardiogram interval, are given.